A Study on Strategic Approaches to Team NIM Games Using Number Theory - Faza, Novan Ramadhani Nur; Kurniadi, Edi; Sylviani, Sisilia (Lembaga Penelitian dan Pengembangan Matematika dan Statistika Terapan Indonesia, PT Anugrah Teknologi Kecerdasan Buatan PT Anugrah Teknologi Kecerdasan Buatan, 2024)
Many games are related to Maths, such as bridge card games, dominoes, chess, NIM, and many others. For example, the NIM game is a strategy game played by two players or two teams in which each player or team takes turns taking at least one object with certain rules. Winning the game depends on how many objects are available and who plays first. In this article, we will present the NIM Maxima game. In this NIM game, the concept of Mathematics that will be used is number theory to determine a strategy to win the game.